PELUANG DARI HADIRNYA TEKNOLOGI DAN E-BUSINESS DI INDONESIA - Utami, Annisa Dwi; Pratama Tarigan, Mhd Agung; Nurbaiti, Nurbaiti (LPPM Universitas Labuhanbatu, 2021)
In this study, the author uses an expansive research type, with a qualitative approach. The research method used is the method of collecting data from various literature sources, then connecting these sources into one. The purpose of this paper is to investigate the foreseeable future readiness of computers. Information technology makes it easier to create creativity and innovation in business. Businesses must see new opportunities. Microsoft provides solutions that